Improving Silat Kick Performance through Muscle Training: Impact on Movement Mechanics and Movement Consistency in South Sulawesi Pencak Silat Athletes - Fahrizal Fahrizal; Arga Arga (Universitas Pejuang Republik Indonesia, 2025)
Background: Kick performance in pencak silat is determined by the interaction of muscle explosive power, movement mechanics, and neuromuscular consistency. Athletes from South Sulawesi who compete in national and regional tournaments require evidence-based training protocols to optimize kicking biomechanics. However, scientific research specifically addressing the effect of muscle training programs on kicking mechanics and movement consistency in South Sulawesi pencak silat athletes remains limited. Objectives: This study aimed to analyze the effect of an 8-week structured muscle training program (combining plyometric and resistance training) on kick velocity, angular velocity, impact force, and movement consistency in pencak silat athletes from South Sulawesi. Methods: A pre-experimental one-group pretest-posttest design was employed. Thirty-two male athletes from South Sulawesi's provincial pencak silat contingent (PELATDA Sulawesi Selatan) were selected by purposive sampling. The training program combined progressive plyometric exercises (squat jumps, box jumps, depth jumps) with resistance training (leg press, hamstring curl, hip flexor strengthening) for 8 weeks, 3 sessions per week. Kick biomechanics including kick velocity (m/s), angular velocity of knee joint (°/s), peak impact force (N), and consistency index were measured using 2D kinematic analysis with Kinovea software and a force pad sensor. Data were analyzed using Paired Sample T-Test (α = 0.05). Results: Significant improvements were found in kick velocity (pre: 7.84 ± 0.93 m/s → post: 9.47 ± 0.81 m/s; p = 0.000), angular velocity (pre: 412.6 ± 38.4 °/s → post: 498.3 ± 32.7 °/s; p = 0.000), peak impact force (pre: 1.247 ± 186.4 N → post: 1.534 ± 164.2 N; p = 0.000), and consistency index (pre: 72.4 ± 8.1% → post: 84.6 ± 6.3%; p = 0.001). Conclusions: A structured 8-week combined plyometric and resistance training program significantly enhances both biomechanical parameters and movement consistency of kicks in South Sulawesi pencak silat athletes, with practical implications for performance coaching and periodization planning.